2022
DOI: 10.1126/sciadv.ade0459
|View full text |Cite
|
Sign up to set email alerts
|

Structure and host specificity of Staphylococcus epidermidis bacteriophage Andhra

Abstract: Staphylococcus epidermidis is an opportunistic pathogen of the human skin, often associated with infections of implanted medical devices. Staphylococcal picoviruses are a group of strictly lytic, short-tailed bacteriophages with compact genomes that are attractive candidates for therapeutic use. Here, we report the structure of the complete virion of S. epidermidis –infecting phage Andhra, determined using high-resolution cryo–electron microscopy, allowing atomic modeling of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
0
12
0
Order By: Relevance
“…The entire structure is shown in the inset. (D) Superposition of the 80a in situ PP (blue) with the PP from phage Andhra (orange; PDB ID: 8EGR) [42].…”
Section: Resultsmentioning
confidence: 99%
“…The entire structure is shown in the inset. (D) Superposition of the 80a in situ PP (blue) with the PP from phage Andhra (orange; PDB ID: 8EGR) [42].…”
Section: Resultsmentioning
confidence: 99%
“…This small podophage is a typical member of the Andhravirus genus (Rountreeviridae family). Like its close relatives, namely Staphylococcus phages Andhra [46,48], BESEP3 (GenBank: MT596500.1), and SeAlphi (NCBI: NC_070880.1), the bacterial host of St_134 is S. epidermidis. Several other coagulase-negative Staphylococcus species were sensitive to St_134, including S. haemolyticus.…”
Section: Discussionmentioning
confidence: 99%
“…The cysteine, histidine-dependent amidohydrolases/peptidases (CHAP) hydrolyze peptidoglycans in the bacterial cell wall. AlphaFold2 showed that the putative 3D structure of LysSte134_2 is similar to the Andhra gp10 protein [46]. In LysSte134_2, the N-terminal globular core contains the predicted enzymatic GyH-like domain and connects to the C-terminal globular CHAP domain via an ordered linker domain (middle linker).…”
Section: In Silico Characterization Of St_134 Lysinsmentioning
confidence: 99%
“…As well as in the case of eukaryotic viruses mentioned above, AlphaFold predictions can contribute to building the model of the viral particle [ 48 , 103 ] or the virion parts, including the attachment apparatus [ 46 , 50 ] and phage egress machinery [ 51 ]. All the steps of phage infection are accompanied by macromolecular interactions that include proteins, so AlphaFold’s highly accurate structural predictions can assist in the elucidation of the mechanisms of the formation of the phage nucleus [ 49 ], lysogeny maintenance [ 53 ] or anti-phage defence [ 44 , 54 ].…”
Section: Application Of Alphafold For Research On Bacteriophagesmentioning
confidence: 99%